‘ADAD DAN MA’DUD DALAM BAHASA ARAB DAN BAHASA INDONESIA (ANALISIS KONTRASTIF) - Irpan Hilmi; Dzati Syauqillah; Yogi Hasbi Sidiq (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
The background that underlies the study of 'adad and ma'dud in Arabic and Indonesian in this research is the failure of learning Arabic, because there is an assumption that Arabic is difficult to learn. Underlying this assumption, among others, is that there are differences in the characteristics of Arabic and Indonesian. This study examines grammatical problems that focus on the study of 'adad and ma'dud in Arabic and Indonesian. The purpose of this thesis is to examine the similarities and differences of 'adad and ma'dud in Arabic and Indonesian and to predict the difficulties that arise from the differences in the structure of the two languages. The type of research used is qualitative research, to be precise, literature or literature study. The data collection method used is documentation analysis (library research), namely collecting data related to the theme of literature books. The data were processed using descriptive methods in terms of presentation and contrastive analysis methods in terms of analysis. Contrastive analysis is an approach to teaching language to bilingual and multilingual students. With this analysis, it is hoped that both teachers and students can make it easier to carry out the language teaching and learning process and be able to minimize the difficulties that arise in understanding and using the language being studied. The results of this study indicate that there are similarities and differences between numbers in Arabic and Indonesian which have been analyzed in the discussion section. The cause of the difficulty is due to differences in the structure of numerals both in Arabic and in Indonesian as well as the interference of the rules of Indonesian as a first language against Arabic as a second language.